Differentially expressed miRNA profiles of serum-derived exosomes in patients with sudden sensorineural hearing loss - Zhang, Juhong; Ma, Haizhu; Yang, Guijun; Ke, Jing; Sun, Wenfang; Yang, Li; Kuang, Shaojing; Li, Hai; Yuan, Wei (Frontiers in Neurology, 2023)
Objectives This study aimed to compare the expressed microRNA (miRNA) profiles of serum-derived exosomes of patients with sudden sensorineural hearing loss (SSNHL) and normal hearing controls to identify exosomal miRNAs that may be associated with SSNHL or serve as biomarkers for SSNHL. Methods Peripheral venous blood of patients with SSNHL and healthy controls was collected to isolate exosomes. Nanoparticle tracking analysis, transmission electron microscopy, and Western blotting were used to identify the isolated exosomes, after which total RNA was extracted and used for miRNA transcriptome sequencing. Differentially expressed miRNAs (DE-miRNAs) were identified based on the thresholds of P < 0.05 and |log2fold change| > 1 and subjected to functional analyses. Finally, four exosomal DE-miRNAs, including PC-5p-38556_39, PC-5p-29163_54, PC-5p-31742_49, and hsa-miR-93-3p_R+1, were chosen for validation using quantitative real-time polymerase chain reaction (RT-qPCR). Results Exosomes were isolated from serum and identified based on particle size, morphological examination, and expression of exosome-marker proteins. A total of 18 exosomal DE-miRNAs, including three upregulated and 15 downregulated miRNAs, were found in SSNHL cases. Gene ontology (GO) functional annotation analysis revealed that target genes in the top 20 terms were mainly related to “protein binding,” “metal ion binding,” “ATP binding,” and “intracellular signal transduction.” Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis revealed that these target genes were functionally enriched in the “Ras,” “Hippo,” “cGMP-PKG,” and “AMPK signaling pathways.” The expression levels of PC-5p-38556_39 and PC-5p-29163_54 were significantly downregulated and that of miR-93-3p_R+1 was highly upregulated in SSNHL. Consequently, the consistency rate between sequencing and RT-qPCR was 75% and sequencing results were highly reliable. Conclusion This study identified 18 exosomal DE-miRNAs, including PC-5p-38556_39, PC-5p-29163_54, and miR-93-3p, which may be closely related to SSNHL pathogenesis or serve as biomarkers for SSNHL.